Digital Marketing Strategies by Utilizing Google Trend Data Analysis on Increasing the Income of Micro, Small and Medium Enterprises (MSMEs) in Sawang, Aceh Utara - Nanda Ameliany; Nursakinah Ritonga; Muchlis Muchlis; Dedi Feriadi Dedi Feriadi; Jamiati KN5 (LPPM Universitas Malikussaleh, 2024)
This research is motivated by the importance of optimizing digital marketing strategies for MSMEs in the digital era, especially in Sawang District, North Aceh. By utilizing Google Trends as a data analysis tool, the research aims to optimize digital[1]based marketing strategies for MSMEs in the region. The research method includes three main stages: 1) Data collection through surveys and short interviews with MSME players and data retrieval from Google Trends; 2) Data analysis using statistical techniques using population and sample size; 3) Development and implementation of digital marketing strategies based on the analysis results. The targeted outputs include an effective digital marketing strategy model for MSMEs, scientific publications, and improved digital marketing skills of MSME players. This research is at Technology Readiness Level (TKT) 6, where the model or design has been tested in a relevant environment. In this context, the developed digital marketing strategy will be tested and implemented on several MSMEs in Sawang Sub-district as samples, to validate its effectiveness and readiness for implementation on a wider scale. Keywords: Data analysis, Google Trends, Digital marketing strategy, MSMEs